PENGARUH KUALITAS PRODUK TERHADAP MINAT KONSUMEN DALAM MEMBELI PRODUK TUPPERWARE PADA PERUMAHAN GRIYA TIKA UTAMA PEKANBARU - Desi Susanti (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2017)
This research aimed to find out the effect of performance, durability, features ofproduct, comformance to specification and reability toward consumer’s interest in buyingTupperware at Griya Tika Utama Housing in Pekanbaru. The population of this researchwas less than 100 so that there were 74 respondences used as the sample of this research.Technique of analyzing data used here was multiple linear regression. In the study theresearcher used a partial hypothesis test (t test) and test hypotheses simultaneously (F test).Based on the results of data analysis, it was shown that models of multiple linearregression equation: Y = 1.885 - 0,199X1 + 0,222X2 + 0,232X3 + 0,174X5 + 0,156X4.From the results of the t test only partially variable of Performance, Durability, Featuresthat significantly influenced consumers' interest in buying Tupperware products at GriyaTika Utama in Pekanbaru. Variable of Conformance to specification and Reliability didnot significantly influenced consumers' interest in buying Tupperware products at GriyaTika Utama in Pekanbaru. From the test results of the analysis of the determinationcoefficient, it was known that the coefficient of determination 0.362 or 36.2% of thevariation of independent variables (Performance, Durability Features, Conformance tospecification, and Reliability) toward the dependent variable (Consumer Interests inbuying the product). While the remaining as 63.8% was explained by other variableswhich were not included in this study.Kata Kunci : Product Quality, Consumer’s Interest